Validation Analysis of Interactive Teaching Materials on Environmental Pollution Integrated with Ethno-Meaningful Learning to Facilitate Students' Knowledge and Creative Thinking Skills - Widia, Widia Efrisa; Asrizal, Asrizal; Hidayati, Hidayat; Yumna, Hayyu (Physics Learning and Education, 2025)
Technological advancements play a vital role in supporting educational processes, particularly in the development of instructional materials. A needs analysis conducted at SMA N 1 Dua Koto revealed that teachers continue to face difficulties in designing technology-based teaching resources. Existing teaching materials have yet to make a significant impact on the improvement of students' knowledge and creative thinking skills. One promising approach to address this issue is the development of interactive teaching materials that integrate ethnoscience and meaningful learning principles. This study aims to evaluate the validity of interactive teaching materials on environmental pollution that are integrated with ethno-meaningful learning. The research employed a Research and Development (R&D) design using the Hannafin and Peck model. The object of the research was the interactive teaching material itself. Data were collected through instruments such as needs analysis questionnaires, validity assessments, and practicality evaluations. The data were analyzed using descriptive statistical methods, particularly Aiken’s V formula. The results of the validation process indicated an average Aiken’s V score of 0.91 which falls into the “valid” category. These findings suggest that the developed teaching materials are both valid and suitable for implementation in classroom settings, with the potential to significantly enhance students’ knowledge and creative thinking skills.